2022
DOI: 10.3989/gya.0441211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of replacing red palm stearin with red palm olein in baked potato cookies

Abstract: Potato cookies were formulated by replacing red palm stearin (RPS) by red palm olein (RPOL) at 0, 17 and 35%, and then baked at 160, 180 and 200 °C for 10, 12 and 15 min. The sensory analysis, using an orthogonal test, showed that a RPS-RPOL ratio of 65:35, baking temperature of 160 ºC, and baking time 12 min were the optimal conditions. Cookies made from 65% RPS + 35% RPOL composition exhibited 0.6 times less squalene, but 1.5 times more β-carotene, tocopherols and tocotrienols than the mixture of RPS and RPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Meanwhile, a study by Canfield et al (2001) found that RPO supplementation in the maternal diet could increase provitamin A in breast milk. Furthermore, research on the use of RPO in various food products such as cookies, cookie cream, chocolate spread and cupcakes provides a new perspective on food products with added nutrition (El-Hadad et al, 2011;Loganathan et al, 2020;Perez-Santana et al, 2021;Mohamad Shah et al, 2022;Xu et al, 2022).…”
Section: Phytonutrient Composition Of Fractionated Rpomentioning
confidence: 99%
“…Meanwhile, a study by Canfield et al (2001) found that RPO supplementation in the maternal diet could increase provitamin A in breast milk. Furthermore, research on the use of RPO in various food products such as cookies, cookie cream, chocolate spread and cupcakes provides a new perspective on food products with added nutrition (El-Hadad et al, 2011;Loganathan et al, 2020;Perez-Santana et al, 2021;Mohamad Shah et al, 2022;Xu et al, 2022).…”
Section: Phytonutrient Composition Of Fractionated Rpomentioning
confidence: 99%